Genetic Characterization of Six Stocks of Litopenaeus vannamei Used in Cuba for Aquaculture by Means of Microsatellite Loci - Anna Pérez-Beloborodova; Adriana Artiles-Valor; Lourdes Pérez-Jar; Damir Hernández-Martínez; Missael Guerra-Aznay; Georgina Espinosa-López (International Journal of Zoology)
Four microsatellite loci were used to achieve genetic characterization of six stocks from Litopenaeus vannamei used for aquaculture in Cuba: second generation from first introduction (S2-1), first generation from the second one (S1-2), from the third one (S1-3), and the fourth one (S1-4) and the crossings from two parental population: first generation from the first with first generation from the third (S1-1 × S1-3) and first generation from the second with first generation from the third (S1-2 × S1-3). 66% (16/24) of genetic systems in total loci were in genetic disequilibrium. The four microsatellite loci were polymorphic for all six stocks. Major quantities of allelic variants correspond to locus Pvan 1758, which is at the same time that one where there are private alleles from first generation of the third. All Fst comparisons were significant. This indicates big differences between stocks. The highest values are those in which there is presence of the second introduction. This introduction and its descendants are also more consanguineous.